2013
DOI: 10.3174/ajnr.a3410
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Degeneration Detected by Combining Voxel-Based Morphometry and Tract-Based Spatial Statistics in Subcortical Strokes with Different Outcomes in Hand Function

Abstract: BACKGROUND AND PURPOSE: Secondary degeneration of the pyramidal tract after focal motor pathway stroke has been observed by diffusion tensor imaging. However, the relationships between outcomes in hand function and secondary degeneration in widespread regions are not well understood. For the first time, we investigated the differences of secondary degeneration across the whole brain between subgroups of patients with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
5
23
0
Order By: Relevance
“…These findings were consistent with previous studies related to subgroups of stroke patients (Yin et al, 2012;Yin, Luo, et al, 2013a;Yin, Yan, et al, 2013b) Corroborating evidence was also documented in several studies between patients and HCs. In addition, the ReHo values in the bilateral CPL were positively correlated with FMA-HW scores, and that in the contralesional SMA was negatively correlated with FMA-HW scores.…”
Section: Full Band Analysis Of Rehosupporting
confidence: 93%
See 2 more Smart Citations
“…These findings were consistent with previous studies related to subgroups of stroke patients (Yin et al, 2012;Yin, Luo, et al, 2013a;Yin, Yan, et al, 2013b) Corroborating evidence was also documented in several studies between patients and HCs. In addition, the ReHo values in the bilateral CPL were positively correlated with FMA-HW scores, and that in the contralesional SMA was negatively correlated with FMA-HW scores.…”
Section: Full Band Analysis Of Rehosupporting
confidence: 93%
“…In addition, the ReHo values in the bilateral CPL were positively correlated with FMA-HW scores, and that in the contralesional SMA was negatively correlated with FMA-HW scores. These findings were consistent with previous studies related to subgroups of stroke patients (Yin et al, 2012;Yin, Luo, et al, 2013a;Yin, Yan, et al, 2013b Corroborating evidence was also documented in several studies between patients and HCs. Patients with motor conversion disorder showed abnormal activity in the SMA during motor preparation compared to that of normal volunteers (Voon, Brezing, Gallea, & Hallett, 2011).…”
Section: Full Band Analysis Of Rehosupporting
confidence: 93%
See 1 more Smart Citation
“…Recently this method has been applied to evaluate white-matter changes of schizophrenia [10, 11] and Parkinson's disease [12]. Yet, few studies have reported stroke-related changes in the WM structural networks using TBSS [1315]. Most of these studies mirrored lesion in one hemisphere to another across the midsagittal axis.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method does not use a symmetric cerebral template and may cause unreliable results. Only one study did not adopt mirror about midline due to enrolling lesions in the same hemisphere [15]. However the lesion locations are not in accordance with clinical practice and greatly limit the subject sample.…”
Section: Introductionmentioning
confidence: 99%